Oocyte yield of GnRH antagonist cycles scheduled with a short course of estradiol in the early follicular phase - Engin Turkgeldi; Sule Yildiz; Berk Angun; Bulent Urman; Baris Ata (IMR Press, 2021)
Scheduling in vitro fertilization cycles enables planning oocyte retrieval and embryology procedures in order to suit both patients' and medical staff's needs. Current methods to schedule ovarian stimulation cycles are either cumbersome, costly or provide minor flexibility. The aim of this study was to investigate if scheduling gonadotropin releasing hormone (GnRH) antagonist cycles with a short course of estradiol in the early follicular phase affects oocyte yield. Fifty-nine oocyte donors undergoing two GnRH antagonist stimulation cycles within 6 months, one with and one without follicular phase estradiol scheduling (FES), serving as their own control were included in this retrospective cohort study. FES was achieved by giving 6 mg/day estradiol valerate orally from the 2n⁢d-3r⁢d day of menstrual cycle until the desired day of gonadotropin start. Main outcome measures were number of cumulus oocyte complexes and metaphase two oocytes. A total of 118 cycles, 59 FES and 59 unscheduled GnRH antagonist, were included. Median duration of estradiol administration was 3 days in FES cycles. In the FES group, stimulation lasted significantly longer by one day (11 vs 10 days, P = 0.03) and total gonadotropin consumption (2497 vs 2404 IU, P = 0.03) was statistically significantly higher, albeit minimal absolute difference, which is probably short of clinical significance. Numbers of COC (21 vs 20) and metaphase-two oocytes (17 vs 17) were similar between the two groups. In conclusion, FES does not require planning in advance and involves shorter use of estradiol/oral contraceptive tablets and can be advantageous to scheduling with luteal estradiol/oral contraceptive administration.